Product’s Attribute and Consumer Perception in Purchasing Decision: the Case of Young Adult’s Yoghurt Consumption - Yasinta Yudya Saraswati; Mujtahidah Anggriani Ummul Muzayyanah; Endang Sulastri (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This research aims to examine the correlation between the attributes and consumer preference for yoghurt. This survey research uses a purposive sampling technique with the criteria age 15-24 years and experiencing to consume yoghurt. Data collection uses an interview approach with a questionnaire as an instrument. A total 257 young adult were selected for this study. The results revealed that consumer perception on yogurt attributes were in